Proceedings of the Third Conference on Partitioned Global Address Space Programing Models 2009
DOI: 10.1145/1809961.1809975
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of UPC programmability using classroom studies

Abstract: Abstract-The study of a language in terms of programmability is a very interesting issue in parallel programming. Traditional approaches in this field have studied different methods, such as the number of Lines of Code or the analysis of programs, in order to prove the benefits of using a paradigm compared to another. Nevertheless, these methods usually focus only on code analysis, without giving much importance to the conditions of the development process and even to the learning stage, or the benefits and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…In [27], the number of lines of code needed by the MPI and the UPC implementations of the NAS Parallel Benchmarks and other kernels are compared. Similar statistical studies with university students are presented in [28] and [29]. These works have demonstrated that the effort needed to solve the same problem is lower in UPC than that in MPI.…”
Section: Related Worksupporting
confidence: 61%
“…In [27], the number of lines of code needed by the MPI and the UPC implementations of the NAS Parallel Benchmarks and other kernels are compared. Similar statistical studies with university students are presented in [28] and [29]. These works have demonstrated that the effort needed to solve the same problem is lower in UPC than that in MPI.…”
Section: Related Worksupporting
confidence: 61%
“…While the ideal approach for programmability analyses involves asking programmers with similar expertise to develop codes and comparing the results [28], this is seldom possible. Therefore, our study relies on objective metrics extracted from the source codes, which is a widely used alternative.…”
Section: Programmability Comparisonmentioning
confidence: 99%
“…The best approach to measure the programmability of different options is probably to rely on the observations and results from a group of programmers with a similar degree of expertise when trying to apply them [29]. This is seldom possible, thus, our study relies on three approximate metrics of this kind.…”
Section: Programmability Comparisonmentioning
confidence: 99%